2013
DOI: 10.1016/j.molcel.2012.12.019
|View full text |Cite
|
Sign up to set email alerts
|

Tet Proteins Connect the O-Linked N-acetylglucosamine Transferase Ogt to Chromatin in Embryonic Stem Cells

Abstract: O-linked N-acetylglucosamine (O-GlcNAc) transferase (Ogt) activity is essential for embryonic stem cell (ESC) viability and mouse development. Ogt is present both in the cytoplasm and the nucleus of different cell types and catalyzes serine and threonine glycosylation. We have characterized the biochemical features of nuclear Ogt and identified the ten-eleven translocation (TET) proteins Tet1 and Tet2 as stable partners of Ogt in the nucleus of ESCs. We show at a genome-wide level that Ogt preferentially assoc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

26
328
1
3

Year Published

2013
2013
2019
2019

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 300 publications
(370 citation statements)
references
References 48 publications
(82 reference statements)
26
328
1
3
Order By: Relevance
“…De nombreux chercheurs ont trouvé en ces enzymes les initiateurs de la déméthylation qu'ils cherchent depuis si longtemps. D'autres y voient de potentiels acteurs dans des maladies affecte leur stabilité ou leur localisation cellulaire [8][9][10]. Un consensus pourrait donc se dévoiler dans lequel les trois TET coopéreraient avec OGT sur la chromatine afin de stabiliser le complexe SET1/ COMPASS, glycosyler l'histone H2B et promouvoir la triméthylation de l'histone H3 ainsi que l'activation de la transcription (voir Figure 1).…”
Section: Discussionunclassified
See 1 more Smart Citation
“…De nombreux chercheurs ont trouvé en ces enzymes les initiateurs de la déméthylation qu'ils cherchent depuis si longtemps. D'autres y voient de potentiels acteurs dans des maladies affecte leur stabilité ou leur localisation cellulaire [8][9][10]. Un consensus pourrait donc se dévoiler dans lequel les trois TET coopéreraient avec OGT sur la chromatine afin de stabiliser le complexe SET1/ COMPASS, glycosyler l'histone H2B et promouvoir la triméthylation de l'histone H3 ainsi que l'activation de la transcription (voir Figure 1).…”
Section: Discussionunclassified
“…Cette activité accrue permet à son tour de glycosyler la sous-unité HCF1 (host cell factor-1) du complexe SET1/ COMPASS, ce qui stabilise le complexe sur la chromatine et promeut la triméthyla-tion de l'histone H3 ainsi que l'activation transcriptionnelle [5]. Ce lien physique et fonctionnel a été confirmé par d'autres laboratoires qui ont également montré que TET1 était capable d'interagir avec OGT dans des cellules embryonnaires murines, et que TET2 participe à la glycosylation d'H2B dépendante d'OGT [7,8]. Plusieurs articles ont également décrit que les trois protéines TET peuvent être à leur tour glycosylées par OGT, ce qui (1) la glycosylation du complexe SET1/COMPASS sur sa sous-unité HCF1, et (2) la glycosylation de l'histone H2B.…”
Section: Potentiels Rôles Du Lien Tet-ogt Dans La Pathogenèseunclassified
“…The interactions were further confirmed in 293T cells [10]. Using a flag-tagged biotinylated form of OGT, Pasini's group found that TET1 and TET2 were stable partners of OGT in mESCs [11]. Deplus et al [12] stated that all TET proteins associated with OGT, whereas TET2 and TET3 had a stronger affinity with OGT than TET1 by using Halo-tagged TET proteins followed by affinity purification.…”
mentioning
confidence: 95%
“…It has been shown that TET proteins associate with either various histone modifications including the methylation of H3K4 and H3K27 or epigenetic regulators such as PRC2 complex and SIN3A co-npg repressor complex [2], suggesting that TET proteins could employ multiple mechanisms to regulate chromatin contexts with respect to the control of gene expression. Notably, three groups recently demonstrated that TET proteins can physically interact with O-linked β-N-acetylglucosamine (O-GlcNAc) transferase (OGT) [10][11][12]. OGT is a unique glycosyltransferase that modifies hundreds of proteins by transferring single O-GlcNAc onto serine/threonine residues, thus participates in signal transduction and transcriptional regulation [11].…”
mentioning
confidence: 99%
See 1 more Smart Citation